THE RESTORATIVE METHOD FOR DEVELOPMENT URGENCY OF CUSTOMARY - Irma Fatmawati; Rahul Ardian Fikri; Mhd Azhali Siregar; Senja Mawarni (Jurnal Ekonomi, 2023)
The study of the administration and distribution of justice in Indonesia is a very important matter to discuss. very important to discuss. First, because Indonesian society is still a pluralistic society. Secondly, the complexity of the law and the issues surrounding the terms 'lex' (legislation, regelgeving) and 'ius' (law, recht). And thirdly, Apeldoorn's opinion that outside the laws there is also law. The Republic of Indonesia is a state of law (rechstaat). In this case, the state should also ensure the upholding of justice by applying and enforcing the existing, including in enforce existing laws, including customary. The implementation of the law can take place normally and peacefully, but it can also be due to violations of the law. also due to violations of the law. In this case, the law that has been violated must be enforced.